2020
DOI: 10.21203/rs.3.rs-52423/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frailty, delirium and hospital mortality of older adults admitted to intensive care: the Delirium (Deli) in ICU study.

Abstract: Background: As the population ages clinical frailty among older adults admitted to intensive care has been proposed as an important determinant of patient outcomes. Among this group of patients an acute episode of delirium is also common, but its relationship to frailty and increased risk of mortality has not been extensively explored. Therefore, the aim of this study was to explore the relationship between clinical frailty, delirium and hospital mortality of older adults admitted to intensive care.Methods: Th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…In addition, cancer and underlying diseases are also associated with patients' in-hospital mortality [39][40][41]. However, there are papers that say that chronological age is not related to inhospital mortality, [42,43], and in elderly patients, malnutrition and frailty were known to be meaningful prognostic factors of in-hospital mortality [43,44]. In addition, Danis et al [45] showed patients and their caregivers were satisfied with ICU treatment, so this may be fully considered before starting ICU treatment for elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cancer and underlying diseases are also associated with patients' in-hospital mortality [39][40][41]. However, there are papers that say that chronological age is not related to inhospital mortality, [42,43], and in elderly patients, malnutrition and frailty were known to be meaningful prognostic factors of in-hospital mortality [43,44]. In addition, Danis et al [45] showed patients and their caregivers were satisfied with ICU treatment, so this may be fully considered before starting ICU treatment for elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Pisani et al did not exclude ICU patients who died during their ICU stay or hospitalization [4]. The occurrence of delirium during hospitalization has been reported to increase hospital mortality among critically ill patients [37]; therefore, we excluded patients with ARDS who had more severe conditions, who might have been diagnosed with delirium, and died during hospitalization. The exclusion of the patients who died within 60 days of ARDS diagnosis may have influenced the results.…”
Section: Discussionmentioning
confidence: 99%
“…[1] In the ICU, delirium is a syndrome manifesting as an acute disturbance and fluctuation of cognition and consciousness characterized by inattention and confusion. [2] It is estimated that delirium could occur in 13% to 66% [3][4][5] of the elderly patients admitted to ICUs, and delirium itself is a known risk factor for poor outcomes, including prolonged ICU and hospital stay, [5] and in-hospital mortality. [3,6] The elderly have been found with brain frailty and less physiologic reserve accompanied by infection, surgery and medication, and thus older patients are more vulnerable to ICU stressors and have a poorer prognosis together with higher medical cost in ICU.…”
Section: Introductionmentioning
confidence: 99%
“…[2] It is estimated that delirium could occur in 13% to 66% [3][4][5] of the elderly patients admitted to ICUs, and delirium itself is a known risk factor for poor outcomes, including prolonged ICU and hospital stay, [5] and in-hospital mortality. [3,6] The elderly have been found with brain frailty and less physiologic reserve accompanied by infection, surgery and medication, and thus older patients are more vulnerable to ICU stressors and have a poorer prognosis together with higher medical cost in ICU. [7][8][9] Unfortunately, although previous studies have found that age is an independent predictor for ICU delirium, [10] there is still a lack of literature addressing the role of aging on delirium outcomes.…”
Section: Introductionmentioning
confidence: 99%